High-durability modified cement-based composite material and preparation method thereof

By adding carbon dot polymers to cement-based materials, the existing rust inhibitors have been solved, and the efficient, economical and environmentally friendly chloride ion resistance effect is achieved, and the durability of reinforced concrete structures is significantly improved. .

CN119430786APending Publication Date: 2025-02-14TAIZHOU UNIV

Patent Information

Application Number
CN202411259152.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing rust resistors have high production costs, poor rust resistance effect, complex production process and insufficient environmental protection, making them difficult to effectively resist chloride ion corrosion, affecting the durability of the reinforced concrete structure.

Method used

The carbon dot polymer is mixed with silicate cement, and high-durability modified cement matrix composite materials are prepared by hydrothermal method or microwave method. The carbon dot polymer plays the role of chloride ion curing agent, reducing porosity and rust inhibitor.

Benefits of technology

It significantly improves the anti-chlorine ion performance of cement-based materials, extends the service life of reinforced concrete structures, reduces production and maintenance costs, and is highly environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430786A_ABST
    Figure CN119430786A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and provides a high-durability modified cement-based composite material and a preparation method thereof.The high-durability modified cement-based composite material comprises a carbon dot polymer, mixing water and Portland cement, and the specific preparation steps are as follows: adding citric acid and urea into water to be dissolved, and then putting into a high-pressure reaction kettle to be heated to obtain an initial product; adding the initial product into water, and carrying out centrifugation, filtration, rotary evaporation and drying to obtain the carbon dots; the preparation method comprises the following steps: dissolving carbon dots in water, preparing an initial carbon dot polymer product by adopting a hydrothermal method or a microwave method, adding the initial carbon dot polymer product into water, centrifuging, filtering, rotationally evaporating and drying to obtain a carbon dot polymer; and mixing the carbon dot polymer with mixing water and Portland cement to obtain the high-durability modified cement-based composite material. The modified cement-based composite material prepared by the invention is simple to prepare, low in cost, green and low-carbon; the rust can be efficiently inhibited, and concrete reinforcements are effectively protected from being corroded; the method can be widely applied to reinforced concrete and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a highly durable modified cement-based composite material and a preparation method thereof. Background Art

[0002] In modern construction projects, reinforced concrete is widely used due to its superior structural performance and economic benefits. However, under various environmental conditions, especially in coastal environments, reinforced concrete is often prone to corrosion such as steel bar rust. Such corrosion phenomena can seriously weaken the bearing capacity and life of the structure, leading to premature aging of the reinforced concrete structure, thereby increasing maintenance costs and possibly causing serious safety accidents.

[0003] In concrete structures, the presence of calcium hydroxide provides an alkaline environment for the steel bars, prompting the formation of a stable passive protective film on the surface of the steel bars, thereby effectively isolating corrosion factors. However, when chloride ions penetrate into the concrete, the pH value of the pore fluid decreases, thereby destroying the passive film on the steel bars. This damage accelerates the corrosion process of the steel bars and greatly shortens the effective service life of reinforced concrete structures. Compared with the steel bar corrosion caused by carbonization of the concrete protective layer, the steel bar corrosion rate caused by chloride ion intrusion is about ten times that of the former, and the damage caused is more serious.

[0004] Chloride ion corrosion is an important factor affecting the durability of reinforced concrete, especially in coastal areas and areas where snow melting agents are used in winter. Chloride ions invade the concrete cover layer, reach the surface of the steel bars and cause corrosion of the steel bars. This corrosion not only reduces the mechanical strength of the structure, but may also lead to a shortened building life and increased maintenance costs. In the field of concrete corrosion protection, although a protective film can be formed on the surface of the steel bars by adding rust inhibitors to isolate corrosive media such as chloride ions and carbonates, thereby delaying the corrosion of steel bars in concrete, traditional rust inhibitors have the disadvantages of poor rust inhibition effect, complex production process and high price. In addition, some rust inhibitors also contain toxic and harmful components, such as chromium-containing compounds and nitrites, which may cause pollution to the environment. Chinese patent CN112811844A discloses a nano-composite migration-type steel bar rust inhibitor suitable for concrete in a marine environment, which includes three components: a high-permeability corrosion inhibition component, a concrete compacting component and a waterproof sealing component. It involves multiple components, the preparation process is complex and the economic and environmental benefits are poor. Chinese patent CN112279546A discloses a composite rust inhibitor for reinforced concrete based on natural gluten. Although gluten is a relatively available resource, its extraction, modification and compounding with other additives may increase costs. Therefore, the development of an economical and environmentally friendly cement-based composite material that can effectively resist chloride ion corrosion is of great significance to improving the durability of reinforced concrete structures and reducing environmental impacts. Summary of the invention

[0005] The purpose of the present invention is to provide a highly durable modified cement-based composite material and a preparation method thereof, aiming to solve the problems of high production cost, poor rust inhibition effect, complex production process and insufficient environmental protection of current rust inhibitors to a certain extent.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The present invention provides a highly durable modified cement-based composite material and a preparation method thereof, comprising a carbon dot polymer, mixing water and silicate cement, wherein the mass ratio of the carbon dot polymer, mixing water and silicate cement is (0.00025-0.02): (0.3-0.5): 1, and the specific preparation steps are:

[0008] S1, adding citric acid and urea in a certain mass ratio to water to dissolve to obtain a mixed solution, placing the mixed solution in a high pressure reactor and heating it at 180-250° C. for 2-3 hours to obtain an initial product, adding the initial product to water, centrifuging, filtering, rotary evaporating, and drying to obtain carbon dots, wherein the mass ratio of citric acid to urea is 6-2:1;

[0009] S2, adding the carbon dots described in S1 into water to dissolve, obtaining a carbon dot mixed solution, preparing an initial carbon dot polymer product by a hydrothermal method or a microwave method, adding the initial carbon dot polymer product into water, centrifuging, filtering, rotary evaporating, and drying to obtain a carbon dot polymer;

[0010] S3. Mix the carbon dot polymer described in S2 with mixing water and silicate cement in a mass ratio to obtain a highly durable modified cement-based composite material.

[0011] Preferably, the hydrothermal method in S2 is to place the carbon dot mixed solution in a high pressure reactor and heat it at 180-300° C. for 2-5 hours, and the microwave method in S2 is to place the carbon dot mixed solution in a microwave reactor with a reaction power of 200-800 W and a reaction time of 1-15 minutes.

[0012] The carbon dots have a particle size of 1 to 10 nm and contain oxygen-containing functional groups and nitrogen-containing functional groups on the surface. The carbon dot polymer is a nearly spherical nanoparticle with a particle size of 10 to 50 nm and contains oxygen-containing functional groups and nitrogen-containing functional groups on the surface. The oxygen-containing functional groups and nitrogen-containing functional groups include one or more of hydroxyl, carboxyl, amide, and imine. Compared with carbon dots, carbon dot polymers are larger in size and have a larger π-π conjugated structure in their carbon core, which makes them play a nucleation effect and defoaming effect like graphene oxide. At the same time, the oxygen-containing functional groups and nitrogen-containing functional groups on the surface of carbon dot polymers make them more dispersible than graphene oxide, so that they can better play a nucleation effect and defoaming effect. On the one hand, the nucleation effect helps to promote cement hydration and generate more hydration products such as hydrated calcium silicate (CSH), monosulfur hydrated calcium sulfoaluminate CS (AFm), etc., thereby promoting the physical adsorption and chemical binding of chloride ions of cement-based materials. Therefore, the carbon dot polymer can play the role of chloride ion curing agent. On the other hand, the defoaming effect helps to reduce the porosity of cement-based materials and prevent the invasion of chloride ions. Therefore, the carbon dot polymer plays a role in reducing porosity. In addition, the oxygen-containing functional groups and nitrogen-containing functional groups on the surface of the carbon dot polymer have strong polarity and can form stable coordination bonds with iron atoms on the surface of steel bars. This chemical bonding helps to form a protective film on the surface of the steel bars, blocking the direct contact between corrosive substances such as moisture and chloride ions and the steel bars. The amide and imine functional groups enhance the protective layer on the surface of the steel bars by forming hydrogen bonds with the surface of the steel bars or interacting with metal ions through the electron donation effect. Therefore, the carbon dot polymer plays the role of a rust inhibitor. It should be noted that the carbon dot particle size is small, and an air entrainment effect will occur, thereby increasing the proportion of harmful pores in the cement-based material and increasing the chloride ion entry channel, which is not conducive to improving the chloride ion resistance of the cement-based material. In summary, carbon dot polymers can play the triple role of chloride ion curing agent, porosity reducing agent, and rust inhibitor, and can more effectively improve the chloride ion resistance of cement-based materials.

[0013] The beneficial effects of the present invention are:

[0014] (1) Sustainable and environmentally friendly raw materials: The carbon dot polymer raw materials used are easy to obtain, widely available, and non-toxic, ensuring the environmental friendliness of the production process. At the same time, the use of this material reduces the need to rely on traditional toxic rust inhibitors and improves the green sustainability standards of concrete materials.

[0015] (2) Significant economic benefits: Since the raw materials are low-cost and easy to process, the present invention greatly reduces the production and maintenance costs and has higher economic benefits compared to traditional rust inhibitors.

[0016] (3) The preparation process is efficient and simple: The preparation method of the present invention does not require complicated equipment or high-energy consumption production processes, simplifies the preparation steps of traditional rust inhibitors, and improves production efficiency.

[0017] (4) Excellent stability: Carbon dot polymers can play a triple role in the concrete matrix: chloride ion curing agent, porosity reduction agent, and rust inhibitor, which significantly improves the stability of the material, enhances its durability in different environments, and effectively extends the service life of reinforced concrete structures.

[0018] (5) High environmental friendliness: The present invention does not use harmful chemicals in the production and application process, which greatly reduces the pollution to the environment and meets the environmental protection requirements of modern building materials. At the same time, by improving the corrosion resistance of steel bars in concrete, the impact on the environment during building maintenance is reduced.

[0019] The present invention will be further explained below in conjunction with the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a preparation flow chart of the present invention. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] A highly durable modified cement-based composite material and a preparation method thereof, comprising a carbon dot polymer, mixing water and silicate cement, wherein the mass ratio of the carbon dot polymer, mixing water and silicate cement is 0.005:0.4:1, and the specific preparation steps are:

[0024] S1, adding citric acid and urea in a certain mass ratio into water to dissolve to obtain a mixed solution, placing the mixed solution into a high-pressure reactor and heating it at 200° C. for 2 h to obtain an initial product, adding the initial product into water, centrifuging, filtering, rotary evaporating, and drying to obtain carbon dots, wherein the mass ratio of citric acid to urea is 4:1;

[0025] S2, adding the carbon dots described in S1 into water to dissolve, obtaining a carbon dot mixed solution, preparing an initial carbon dot polymer product by a hydrothermal method or a microwave method, adding the initial carbon dot polymer product into water, centrifuging, filtering, rotary evaporating, and drying to obtain a carbon dot polymer;

[0026] S3. Mix the carbon dot polymer described in S2 with mixing water and silicate cement in a mass ratio to obtain a highly durable modified cement-based composite material.

[0027] Furthermore, the hydrothermal method in S2 is to place the carbon dot mixed solution in a high pressure reactor and heat it at 200° C. for 3 hours, and the microwave method in S2 is to place the carbon dot mixed solution in a microwave reactor with a reaction power of 500 W and a reaction time of 5 minutes.

[0028] Furthermore, the particle size of the carbon dot aggregate is 10 to 50 nm.

[0029] Example 2

[0030] The difference from Example 1 is that the mass ratio of carbon dot polymer, mixing water and silicate cement is 0.02:0.4:1.

[0031] Comparative Example 1

[0032] The mixing water and silicate cement are mixed in a mass ratio of 0.4:1 to obtain a cement-based material.

[0033] Comparative Example 2

[0034] It includes carbon dots, mixing water and silicate cement, wherein the mass ratio of carbon dots, mixing water and silicate cement is 0.02:0.4:1. The specific preparation steps are: adding citric acid and urea in a certain mass ratio into water to dissolve to obtain a mixed solution, placing the mixed solution into a high-pressure reactor and heating it at 200°C for 2 hours to obtain an initial product, adding the initial product into water to obtain carbon dots after centrifugation, filtration, rotary evaporation and drying, wherein the mass ratio of citric acid to urea is 4:1; mixing the carbon dots described in S2 with mixing water and silicate cement in a mass ratio to obtain a modified cement-based composite material.

[0035] Furthermore, in order to verify the advancement of a highly durable modified cement-based composite material and a preparation method thereof provided in Examples 1 and 2 of the present invention, the chloride ion corrosion resistance and compressive strength of the cement-based materials prepared in Examples 1, 2, Comparative Example 1 and Comparative Example 2 were tested by the following test methods.

[0036] 1. Chloride ion corrosion resistance test

[0037] The cement-based material was poured into a 1.5 cm × 1.5 cm × 1.5 cm silicone mold, covered with a plastic film and placed in a curing room for 24 hours before demolding. The demolded sample was placed in a curing room for curing for 28 days.

[0038] Cut the hardened cement test block into small pieces of 10mm×10mm×10mm, and try to keep the surface of the sample flat and without defects. Dry the cut sample in a vacuum drying oven at 105℃, dry for 24 hours and then cool to room temperature. Test the porosity of the sample according to GB / T 21650.1-2008 "Mercury Intrusion and Gas Adsorption Method for Determination of Pore Size Distribution and Porosity of Solid Materials Part 1: Mercury Intrusion Method".

[0039] Grind the test block that has been cured for 28 days and sieve it to 0.15mm. Place the sieved powder in a vacuum drying oven for 7 days to obtain a powder sample. Dissolve NaCl particles in deionized water to prepare a NaCl solution with a concentration of 3 mol / L. Take 5g of the dried powder sample and 50ml of the prepared NaCl solution and place them in a sealed container, stir them thoroughly, and let them stand for 14 days to obtain a solid-liquid mixture.

[0040] The solid-liquid mixture was placed in a high-speed centrifuge and centrifuged at 3500 rpm for 5 min to obtain the supernatant. The supernatant was taken out and titrated with 0.01 mol / L silver nitrate solution using an automatic point titration instrument according to the national standard JGJT 322-2013 "Technical Specification for Chloride Ion Content in Concrete" to obtain the residual chloride ion content in the supernatant. The formula C b =35.45*(Ci-Ce)*V SCHS / m total Calculation) to obtain the chloride ion content adsorbed by the cement-based composite material, see Table 1, where 35.45 is the molar mass of chloride ions, Ci is the initial chloride ion concentration (mol / L); Ce is the free chloride ion concentration (mol / L); V SCHS is the volume of saturated calcium hydroxide solution (ml); m total is the sample mass (g).

[0041] 2. Mechanical properties testing

[0042] The freshly mixed slurry was added into a mold of 40mm×40mm×40mm, and placed in a curing room with a temperature of 20±2°C and a relative humidity greater than 95% for curing for 28 days to obtain hardened cement test blocks of Comparative Example 1, Comparative Example 2, Example 1 and Example 2.

[0043] Referring to GB / T17671-2021 "Test method for strength of cement mortar (iso method)", the compressive strength test of the hardened cement test blocks of Comparative Example 1, Comparative Example 2, Example 1 and Example 2 was carried out.

[0044] As shown in Table 1, in Example 1, the total porosity is 20.53%, which is 10.0% lower than that in Comparative Example 1 and 17.9% lower than that in Comparative Example 2; the harmless pore ratio is 19.45%, which is 20.9% higher than that in Comparative Example 1 and 23.7% higher than that in Comparative Example 2; the harmful pore ratio is 10.64%, which is 21.3% lower than that in Comparative Example 1 and 17.0% lower than that in Comparative Example 2. In Example 2, the total porosity is 21.43%, which is 6.0% lower than that in Comparative Example 1 and 14.4% lower than that in Comparative Example 2; the harmless pore ratio is 21.54%, which is 34.0% higher than that in Comparative Example 1 and 37.0% higher than that in Comparative Example 2; the harmful pore ratio is 9.57%, which is 29.2% lower than that in Comparative Example 1 and 25.4% lower than that in Comparative Example 2.

[0045] As shown in Table 2, in Example 1, when the mass of the carbon dot polymer is 2.5g, the chloride ion adsorption is 37.3629mg / g, which is 30.8% higher than that of Comparative Example 1 and 22.6% higher than that of Comparative Example 2; the 28d compressive strength is 47.6MPa, which is 3.9% higher than that of Comparative Example 1 and 3.0% higher than that of Comparative Example 2. In Example 2, when the mass of the carbon dot polymer is 10g, the chloride ion adsorption is 43.7659mg / g, which is 53.2% higher than that of Comparative Example 1 and 43.6% higher than that of Comparative Example 2; the 28d compressive strength is 48.0MPa, which is 4.8% higher than that of Comparative Example 1 and 3.9% higher than that of Comparative Example 2.

[0046] Table 1 Sample porosity results

[0047]

[0048]

[0049]

[0050] Table 2 Chloride ion adsorption and compressive strength results

[0051] It can be seen that the chloride ion adsorption effect of the high-durability modified cement-based composite material prepared by the present invention is significantly improved, and the 28d compressive strength is improved.

[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the appended claims and their equivalents.

Claims

1. A highly durable modified cement-based composite material and a preparation method thereof, characterized in that: The method comprises carbon dot polymer, mixing water and silicate cement, wherein the mass ratio of carbon dot polymer, mixing water and silicate cement is (0.00025-0.02):(0.3-0.5):1, and the specific preparation steps are as follows: S1, adding citric acid and urea in a certain mass ratio to water to dissolve to obtain a mixed solution, placing the mixed solution in a high pressure reactor and heating it at 180-250° C. for 2-3 hours to obtain an initial product, adding the initial product to water, centrifuging, filtering, rotary evaporating, and drying to obtain carbon dots, wherein the mass ratio of citric acid to urea is 6-2:1; S2, adding the carbon dots described in S1 into water to dissolve, obtaining a carbon dot mixed solution, preparing an initial carbon dot polymer product by a hydrothermal method or a microwave method, adding the initial carbon dot polymer product into water, and obtaining a carbon dot polymer after centrifugation, filtration, rotary evaporation, and drying; S3. Mix the carbon dot polymer described in S2 with mixing water and silicate cement in a mass ratio to obtain a highly durable modified cement-based composite material.

2. A highly durable modified cement-based composite material according to claim 1, characterized in that: The hydrothermal method in S2 is to place the carbon dot mixed solution in a high pressure reactor and heat it at 180-300° C. for 2-5 hours. The microwave method in S2 is to place the carbon dot mixed solution in a microwave reactor with a reaction power of 200-800W and a reaction time of 1-15 minutes.

3. A highly durable modified cement-based composite material according to claim 1, characterized in that: The particle size of the carbon dot aggregate is 10 to 50 nm.

Citation Information

Patent Citations

  • Composite corrosion inhibitor based on natural glutelin and used for reinforced concrete

    CN112279546A

  • Nano composite migration type steel bar corrosion inhibitor suitable for concrete in marine environment

    CN112811844A

Cited By

  • Ferroaluminate cement with low hydration heat and preparation method thereof

    CN120398447A

  • Preparation method of high-strength and high-durability 3D printing concrete

    CN121292908A